Penghayatan Keteladanan Maria dalam Membangun Keluarga Harmonis di Stasi Santo Paulus Sampun - Mayda Br Ginting; Paulus Halek Bere (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to describe the appreciation of the exemplary role of the Virgin Mary in building harmonious families in the St. Paul Sampun Congregation. In the Catholic tradition, Mary is seen as a model of faith, love, faithfulness, and humility. These values ​​inspire Catholics in building family lives rooted in God's love. This study uses a descriptive qualitative approach, with data collection techniques consisting of in-depth interviews, participant observation, and documentation of Catholics who are considered to have a deep spirituality towards Mary. The results show that Mary's exemplary role is concretely lived in the lives of the congregation's families, reflected through four main dimensions: hope in God, a spirit of mutual support, sincere love, and humility. Catholic families in the St. Paul Sampun Congregation cultivate the habit of praying together, building caring and understanding relationships, and demonstrating an attitude of mutual forgiveness in their daily lives. These values ​​align with Mary's example of faithfully accompanying Jesus throughout all stages of His life. Thus, appreciation for Mary's exemplary role proves to be a solid foundation in building harmonious, faith-filled, and loving Catholic families. It is hoped that these findings will enrich the pastoral development of families and strengthen the spirituality of the congregation in family life.